Performance of pre and post-emergence herbicides in Bt-cotton crop - Singh, Harpreet; Manhas, S.S. (Annals of Agricultural Research, 2016)
A field experiment was carried out at Bathinda during kharif- 2013 to study the performance of pre and post-emergence herbicides in Bt-cotton crop. The experiment was laid out in randomized block design with 8 treatments and 3 replications. Results revealed that all herbicides either applied alone or in combination significantly reduced the weed population and dry matter accumulation in comparison to weedy check. Application of Pyrithiobac Sodium @ 62.5 g/ha followed by Quizalofopethyl 50 g/ha both at 2-4 weed leaf stage + One Hoeing at 40-60 days after sowing (DAS) significantly reduced weed population and dry matter accumulation as compared to other treatments. The maximum growth parameters, yield attribute and yield were recorded with the application of Pyrithiobac Sodium @ 62.5 g/ha followed by Quizalofopethyl 50 g/ha both at 2-4 weed leaf stage + One Hoeing at 40-60 DAS which was at par with Pendimethalin @ 1000 g/ha + Quizalofopethyl @ 50 g/ha at 2-4 weed leaf stage + One Hoeing at 40-60 DAS and significantly higher than other treatments of weed control.Net monetary returns (103403 Rs/ha) and benefit cost ratio (2.30) was observed with Pyrithiobac Sodium @ 62.5 g/ha followed by Quizalofopethyl 50 g/ha both at 2-4 weed leaf stage + One Hoeing at 40-60 DAS which was at par with Pendimethalin @ 1000 g/ha + Quizalofopethyl @ 50 g/ha at 2-4 weed leaf stage + One Hoeing at 40-60 DAS and significantly higher than other treatments of weed control.